Reverse chemical ecology-based approach leading to the accidental discovery of repellents for Rhodnius prolixus, a vector of Chagas diseases refractory to DEET. (December 2018) - Franco, Thiago A.; Xu, Pingxi; Brito, Nathália F.; Oliveira, Daniele S.; Wen, Xiaolan; Moreira, Monica F.; Unelius, C. Rikard; Leal, Walter S.; Melo, Ana C.A.
Abstract: Rhodnius prolixus is one of the most important vectors of Chagas disease in Central and South America for which repellents and attractants are sorely needed. Repellents like DEET, picaridin, and IR3535 are widely used as the first line of defense against mosquitoes and other vectors, but they are ineffective against R. prolixus. Our initial goal was to identify in R. prolixus genome odorant receptors sensitive to putative sex pheromones. We compared gene expression of 21 ORs in the R. prolixus genome, identified 4 ORs enriched in male (compared with female) antennae. Attempts to de-orphanize these ORs using the Xenopus oocyte recording system showed that none of them responded to putative sex pheromone constituents. One of the them, RproOR80, was sensitive to 4 compounds in our panel of 109 odorants, namely, 2-heptanone, γ-octalactone, acetophenone, and 4-methylcychohexanol. Interestingly, these compounds, particularly 4-methylcyclohexanol, showed strong repellency activity as indicated not only by a significant decrease in residence time close to a host, but also by a remarkable reduction in blood intake. 4-Methylcyclohexanol-elicited repellency activity was abolished in RNAi-treated insects. In summary, our search for pheromone receptors led to the discovery of repellents for R. prolixus . Graphical abstract: Highlights: qPCR showed that out of 21 candidate pheromone receptors in Rhodnius prolixus genome, 4 genes were enriched in male antennae. Deorphanization with the Xenopus oocyte expression system demonstrated that none of 4 receptors responded to sex pheromones. One receptor, RproOR80, was sensitive to 2-heptanone, g-octalactone, acetophenone, and 4-methylcyclohexanol. [Please use gamma for g-octalactone]. With these compounds, nymphs spent less time close to a human host and did not take a blood meal from a vertebrate host. Repellency activity was abolished in RproOR80-dsRNA-injected nymphs, but not in controls injected with water or β-GAL-dsRNA.